Antioxidant Activities of Beetroot (Beta vulgaris L.) Extracts - Nahla, T.K.; Wisam, S.U.; Tariq, N.M. (Pakistan Journal of Nutrition, 2018)
Background and Objective: Beetroot (Beta vulgaris L.) is one of the most commonly produced vegetables around the world, recently, plant extracts containing phenolic compounds have been screened to find new natural food ingredients. The antioxidant activity of phenolic compounds is mainly due to their redox properties, which can play an important role in their ability to chelate and neutralize free radicals, quench singlet and triplet oxygen and decompose peroxides. This study was designed to determine the antioxidant activity of the aqueous and ethanolic extracts of beetroot by using two different methods. Methodology: The samples of beetroot were locally obtained, cleaned and ground. Twenty grams of the ground material was extracted with 250 mL of distilled water or 95% ethanol at reflux for 1 h. The extract was filtered and concentrated at 50°C for dryness. Results: The phenolic compounds and flavonoids in the ethanolic extract of beetroot were 16.88 and 10.80%, respectively, of the mass of the extract and their contents in the aqueous extract were 7.812 and 4.77%, respectively. The reducing powers of the ethanolic and aqueous extracts were also determined. The reducing power was increased by increasing the sample concentration and reached 88.89% for the ethanolic and 80.89% for the aqueous extract. The aqueous extract showed a lower chelating capacity than EDTA (absorbances of 53.98 and 93.00, respectively) and a lower capacity than that of the ethanolic extract, which had an absorbance of 68.11. Conclusion:It is concluded that natural antioxidants from edible sources are considered safer alternatives to synthetic antioxidants for food preservation.